Meningkatan Civic Participatory Skill Melalui Model Window Shopping untuk Membentuk Keterampilan Komunikasi dan Kolaborasi - Muhamad Ilham Maulana; Harianingsih; Ellianawati; Decky Avrilianda (Sosio-Didaktika: Social Science Education Journal, 2025)
21st-century learning requires learners to have communication skills, collaboration, and active participation. These skills strengthen civic participatory abilities. This study aims to analyze the use of the cooperative learning model, the Window Shopping type. The goal is to improve civic participatory skills by strengthening communication and collaboration in Pancasila education. The research uses a qualitative case study approach at SMP Negeri 12 Depok. Data were collected through interviews, observations, and documentation. The analysis was conducted qualitatively, using a descriptive approach. The results showed that applying the cooperative learning model, the Window Shopping type, encourages learners to interact, argue, and work together in a democratic learning atmosphere. The learning process becomes more participatory, reflective, and collaborative. These changes strengthen communication, collaboration, and civic participation. Thus, the cooperative learning model, Window Shopping type, is effective for developing civic participatory skills in Pancasila education for 21st-century learners. Keywords: Cooperative Learning, Window Shopping, Civic Participatory Skill, Civic Skill, Pancasila Education